Choroid plexus CCL2‒CCR2 signaling orchestrates macrophage recruitment and cerebrospinal fluid hypersecretion in hydrocephalus - Qiguang Wang; Fei Liu; Yue Li; Huan Zhang; Xin Qi; Ke Wu; Yi Zhang; Shenglan You; Wenke Liu; Xuhui Hui; Hanmei Li; Lei Zhu; et al. (Elsevier, 2024)
The choroid plexus (ChP) serves as the principal origin of cerebrospinal fluid (CSF). CSF hypersecretion due to ChP inflammation has emerged as an important pathogenesis of hydrocephalus recently. Nevertheless, the precise mechanisms of ChP inflammation and the ensuing CSF hypersecretion in hydrocephalus remain ill-defined. In the present study, we elucidate the critical role of macrophages in the pathogenesis of ChP inflammation. Specifically, we identify the chemokine CCL2, released by ChP epithelial cells, recruits CCR2+ monocytes to the ChP thereby inciting hydrocephalus pathogenesis. The accumulated ChP macrophages increase the inflammation in ChP epithelial cells through TNF-α/TNFR1/NF-κB signaling cascade, thereby leading to CSF hypersecretion. Strikingly, augmentation of ChP‒CCL2 using an adeno-associated viral approach (AAV) exacerbates macrophage recruitment, activation, and ventriculomegaly in rat PHH models. Systemic application of Bindarit, a specific CCL2 inhibitor, significantly inhibits ChP macrophage infiltration and activation and reduces CSF secretion rate. Furthermore, the administration of CCR2 antagonist (INCB 3284) reduces ChP macrophage accumulation and ventriculomegaly. This study not only unveils the ChP CCL2‒CCR2 signaling in the pathophysiology of hydrocephalus but also unveils Bindarit as a promising therapeutic choice for the management of posthemorrhagic hydrocephalus.